CO07 | Real word management of anticoagulant therapy in brain metastasis: moving toward a multidisciplinary approach in complex cases (Bleeding, Thrombosis and Vascular Biology)
Background: Patients with advanced solid tumors have an increased risk of thrombosis and are often on anticoagulation treatment with low molecular weight heparin (LMWH) or the new oral anticoagulant drugs (DOACs). Brain metastases (BMs) have an increased risk of intracranial bleeding (ICH), depending on systemic and locoregional treatments. However, existing literature consists of small case series, and prospective studies of LMWH and DOACs do not include BMs’ patients. Our study aims to describe the impact of adverse events related to anticoagulant therapy, in a real word setting in patients with BMs.